America’s Other Growth Rate: What the U.S. Obesity Epidemic and Healthcare Cost Crisis Mean for the Rest of the World - Dhillon, Ranu (Consilience, 2014)
Increasing obesity rates in the United States have fueled soaring healthcare costs and exacerbated recent fiscal and economic challenges. This phenomena, however, is not unique to the U.S. and many countries, including low and middleincome countries, are seeing increasing numbers of people who are obese or overweight. Finding ways for societies to achieve the benefits of economic growth without suffering concurrent epidemics of obesity and related diseases represents a central challenge to sustainable development. For countries where this epidemic has already taken hold, new policy thinking is needed to mitigate this burden. Meanwhile, emerging nations must define new pathways for development that bypass or minimize these pitfalls. Proactive public policies, innovations in healthcare delivery, and refashioning the lifestyles adopted with growth represent potential avenues through which countries can navigate this issue.